Clinical Significance of GNAS Mutation in Intraductal Papillary Mucinous Neoplasm of the Pancreas With Concomitant Pancreatic Ductal Adenocarcinoma. Issue 2 (March 2015) - Ideno, Noboru; Ohtsuka, Takao; Matsunaga, Taketo; Kimura, Hideyo; Watanabe, Yusuke; Tamura, Koji; Aso, Teppei; Aishima, Shinichi; Miyasaka, Yoshihiro; Ohuchida, Kenoki; Ueda, Junji; Takahata, Shunichi; et al.
Abstract : Objective: The aims of this study were to investigate the GNAS mutational status in pancreatic intraductal papillary mucinous neoplasm (IPMN) with and without distinct pancreatic ductal adenocarcinoma (PDAC) and to evaluate the significance of GNAS analysis using duodenal fluid (DF) in patients with IPMN. Methods: The clinicopathologic features of 110 patients with IPMN including 16 with distinct PDAC were reviewed. The GNAS status in the IPMN tissue and 23 DF specimens was assessed by sensitive mutation scanning methods. Results: The GNAS mutation rate in IPMN with distinct PDAC was significantly lower than that in IPMN without PDAC (4/16, 25%, vs 61/94, 65%; P = 0.0047). By multivariate analysis, GNAS wild-type and gastric type IPMNs were significantly associated with distinct PDAC. Of 45 GNAS wild-type IPMNs, 10 (43%) of 23 gastric type IPMNs had distinct PDAC, whereas only 2 (9%) of 22 non–gastric type IPMNs had distinct PDAC ( P = 0.017). The GNAS status in DF was consistent with that in tissue in 21 (91%) of 23 patients. Conclusions: Distinct PDACs frequently develop in the pancreas with gastric type IPMN without GNAS mutations. Duodenal fluid DNA test would predict the GNAS status of IPMN, whereas the detection of the gastric subtype using noninvasive test remains to be determined. Abstract : Supplemental digital content is available in the text.